1995
DOI: 10.1002/eji.1830250309
|View full text |Cite
|
Sign up to set email alerts
|

Heparin inhibits the antiparasitic and immune modulatory effects of human recombinant interferon‐γ

Abstract: Interferon-gamma (IFN-gamma) is a potent immune regulatory cytokine and is, in addition, involved in the induction of antiparasitic effector mechanisms in different cell types. The first step of IFN-gamma action is its binding to a specific receptor. Furthermore, it has been shown that IFN-gamma binds with a great affinity to the heparin-like structure of heparan sulfate, which is localized in basement membranes and on cell surfaces. In this study, we analyze the effect of heparin and heparan sulfate on three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…In conclusion, results presented in this study appear to demonstrate that IFN-g binds initially to endothelial cells by interaction between basic amino acids located within the C-terminal region of the molecule and HS-containing PG on the cell surface, confirming the theory proposed previously by several groups, including ourselves [19,21,34]. This interaction is shown to be necessary for optimal proinflammatory activation of endothelial cells.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, results presented in this study appear to demonstrate that IFN-g binds initially to endothelial cells by interaction between basic amino acids located within the C-terminal region of the molecule and HS-containing PG on the cell surface, confirming the theory proposed previously by several groups, including ourselves [19,21,34]. This interaction is shown to be necessary for optimal proinflammatory activation of endothelial cells.…”
Section: Discussionsupporting
confidence: 91%
“…However, tight adhesion to endothelium can also be regulated by changes in the expression of ICAM-1 induced by cytokines such as IFN-and TNF-which are produced during the development of inflammatory lesions. It has been reported previously by this group [19], and others [20], that heparin can antagonize the induction of class II MHC molecules by IFN-. In this study it is shown for the first time that heparin can also antagonize the up-regulation of ICAM-1 by IFN--treated HUVEC.…”
Section: Discussionmentioning
confidence: 69%
“…Soluble GAG were found to interfere with the activity of IL-10 or IFN-γ [9,10,114,173]. Heparin can also neutralize chemoattractants released from platelets such as PF-4 and RANTES [174].…”
Section: Blockade Of Cytokine Chemokine or Growth Factor Activitiesmentioning
confidence: 99%